Particle sources and downward fluxes in the eastern Fram strait under the influence of the west Spitsbergen current. (September 2015) - Sanchez-Vidal, Anna; Veres, Oriol; Langone, Leonardo; Ferré, Benedicte; Calafat, Antoni; Canals, Miquel; Durrieu de Madron, Xavier; Heussner, Serge; Mienert, Jurgen; Grimalt, Joan O.; Pusceddu, Antonio; Danovaro, Roberto
Abstract: The carbon cycle of the Arctic Ocean is tightly regulated by land–atmosphere–cryosphere–ocean interactions. Characterizing these environmental exchanges and feedbacks is critical to facilitate projections of the carbon cycle under changing climate conditions. The environmental drivers of sinking particles including organic carbon (OC) to the deep-sea floor are investigated with four moorings including sediment traps and currentmeters at the Arctic gateway in the eastern Fram Strait, which is the area where warm anomalies are transported northwards to the Arctic. Particles fluxes were collected over one year (July 2010–July 2011) and have been analysed to obtain the content of the lithogenic fraction, calcium carbonate, OC and its stable isotopes, opal, and the grain size. Records of near bottom current speed and temperature along with satellite observations of sea ice extent and chlorophyll-a concentration have been used for evaluation of the environmental conditions. We found increased lithogenic fluxes (up to 9872 mg m −2  d −1 ) and coarsening grain size of settling particles in late winter–early spring. At the same time, intensifications of the northward flowing west Spitsbergen current (WSC) were recorded. The WSC was able to resuspend and transport northwards sediments that were deposited at the outlet of Storfjordrenna and on the upper slope west of Spitsbergen. The signal of recurrent winnowing of fine particles was also detected in the top layer of surface sediments. In addition, an increased arrival of sea ice transported ice rafted detritus (>414 detrital carbonate mineral grains larger than 1 mm per m 2 ) from the southern Spitsbergen coast along with terrestrial organic matter was observed beyond 1000 m of water depth during winter months. Finally, the downward particle fluxes showed typical temporal variability of high latitudes, with high percentages of the biogenic compounds (opal, organic carbon and calcium carbonate) linked to the phytoplankton bloom in spring–summer. However, on an annual basis local planktonic production was a secondary source for the downward OC, since most of the OC was advected laterally by the WSC. Overall, these observations demonstrated the sensitivity of the downward flux of particles to environmental conditions such as hydrodynamics, sea ice rafting, and pelagic primary production. Future alteration of the patterns of natural drivers due to climate change is thus expected to cause major shifts in the downward flux of particles, including carbon, to the deep sea ecosystems. Highlights: Downward flux of particles in the western Spitsbergen margin during one year is reported. Particle fluxes and carbon fluxes are strongly sensitive to environmental conditions. The west Spitsbergen current resuspended and transported sediments northwards. Settling of sea ice-transported IRDs impacted sedimentary and carbon dynamics. Pelagic settling of carbon represented <28% of the carbon reaching annually the seafloor.